Investigação de correlatos neurais da apatia na variante comportamental da demência frontotemporal - Simone de Andrade Baião Gonçalves (2019)
Introduction The behavioral variant of frontotemporal dementia (bvFTD) is the second most common cause of young-onset neurodegenerative dementia. Apathy is the most prevalent neuropsychiatric disorder in bvFTD. The neural basis of apathy in bvFTD is still poorly understood. We investigated the neural basis of apathy in bvFTD, through structural neuroimaging study. Methods We included patients with probable bvFTD (n = 21) and healthy controls (HC, n = 22). Participants were matched for age, sex and schooling. All subjects underwent a thorough neuropsychological examination, including tests for executive functions and social cognition. Apathy was assessed with Starkstein Apathy Scale (SAS). All subjects underwent 3T brain MRI. We investigated correlations between SAS scores and gray matter atrophy in the bvFTD group. Executive function (Frontal Assessment Battery) and disease severity were considered as covariates in neuroimaging analyses. Results Compared to HC, bvFTD patients had lower scores on global cognitive efficiency, executive functions and social cognition. All bvFTD had clinically relevant apathy (scores greater than 14 in the SAS). Performance in executive function tests did not correlate with apathy scores. The severity of apathy was negatively correlated with gray matter volumes in midline prefrontal regions namely, orbitofrontal cortex and both anterior and dorsal regions of cingulate cortex. Conclusions Apathy in bvFTD is related to a specific network of prefrontal cortical areas critically involved in effort-based decision-making for rewards. Further studies may clarify the neural correlates of apathy and its heterogeneous manifestations in bvFTD. Keywords: Behavioral variant frontotemporal dementia, apathy, MRI.